Events Associated with Early Age-Related Decline in Adventitious Rooting Competence of Eucalyptus globulus Labill - Aumond, Márcio L.; de Araujo, Artur T.; de Oliveira Junkes, Camila F.; de Almeida, Márcia R.; Matsuura, Hélio N.; de Costa, Fernanda; Fett-Neto, Arthur G. (Frontiers in Plant Science, 2017)
The development of adventitious roots is affected by several factors, including the age of the cutting donor plant, which negatively affects rooting capacity. Eucalyptus globulus quickly loses rooting capacity of cuttings as the donor plant ages, although the molecular and biochemical mechanisms behind this process are still unclear. To better understand the bases of rooting competence loss in E. globulus, the time required for a significant decline in rhizogenic ability without exogenous auxin was determined in microcuttings derived from donor plants of different ages after sowing. Tip cuttings of donor plants were severed before and after loss of rooting competence of microcuttings to test the hypothesis that auxin and carbohydrate homeostasis regulate rooting competence decline. There were no significant changes in concentration of carbohydrates, flavonoids, or proteins before and after the loss of rooting capacity. Peroxidase (EC 1.11.1.7) total activity increased with loss of rooting competence. Auxin concentration showed the opposite pattern. In good agreement, TAA1, a key gene in auxin biosynthesis, had lower expression after loss of rooting capacity. The same applied to the auxin receptor gene TIR1, suggesting reduced auxin sensitivity. On the other hand, genes associated with auxin response repression (TPL, IAA12) or with the action of cytokinins, the rhizogenesis inhibitor-related ARR1, showed higher expression in plants with lower rooting competence. Taken together, data suggest that age negatively affects E. globulus rooting by a combination of factors. Decreased endogenous auxin concentration, possibly caused by less biosynthesis, lower auxin sensitivity, higher expression of genes inhibiting auxin action, as well as of genes related to the action of cytokinins, appear to play roles in this process.